Ombudsmen needed in varsities - Omoola, Sodiq Olalekan (New Straits Times Press (M) Bhd., 2018)
The complaint handling policy in the education sector for students is contained in the code of practice for programme accreditation, which, in paragraph 4.4.1, states: “There must be a mechanism for students to air grievances and make appeals relating to student support services.”